The educational philosophy Pengembangan Pembelajaran Sains Anak Usia Dini (Tinjauan Filsafat Pendidikan dalam Pendidikan Awal) : The educational philosophy - Badri Munawar; Suyitno Muslim; Wisnu Djatmiko (Metakognisi, 2025)
This research explores the development of early childhood science learning through an educational philosophy approach. This research discusses the development of early childhood science learning, including questions, viewpoint formation, rationality, information seeking, and analysis. This research uses the literature review method, namely data obtained through literature from journals, articles and book references to form a solid basis with the analysis techniques carried out, namely data reduction, data presentation and drawing conclusions. The results of this research on ontological, epistemological and axiological aspects contribute to a deeper understanding of the role of educational philosophy in the development of early childhood science learning.